PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS MATEMATIKA REALISTIK PADA MATERI BARISAN DAN DERET UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI SISWA DI MADRASAH ALIYAH MAMBAUL ULUM BANJAREJO [DEVELOPMENT OF REALISTIC MATHEMATICS-BASED STUDENT WORKSHEETS ON SEQUENCES AND SERIES TO IMPROVE STUDENTS’ NUMERACY LITERACY SKILLS AT MAMBAUL ULUM BANJAREJO ISLAMIC SENIOR HIGH SCHOOL] - Annanda Shofi Sulthoni; Ucik Fitri Handayani (JOHME: Journal of Holistic Mathematics Education, 2026)
Mathematics instruction should be supported by contextual learning materials that enable students to understand concepts meaningfully and enhance their numeracy skills. However, mathematics learning at MA Mambaul Ulum Banjarejo is still largely dominated by abstract textbooks, resulting in students experiencing difficulties in understanding the concepts of sequences and series. Therefore, there is a need to develop student worksheets based on the Realistic Mathematics Education (RME) approach that connect mathematical concepts with students’ everyday experiences. This study aimed to develop RME-based student worksheets that are valid, practical, and effective in improving students’ numeracy literacy skills on the topic of sequences and series. The study employed the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants were tenth-grade students at Madrasah Aliyah Mambaul Ulum Banjarejo. Data were collected through interviews, observations, questionnaires, and tests. The validation results indicated that the developed worksheets achieved a validity score of 80%, categorized as highly valid. The practicality level reached 87.5%, indicating that the worksheets were highly practical for classroom use. Furthermore, the implementation results revealed a significant improvement in students’ numeracy literacy skills before and after using the worksheets, as demonstrated by the paired-samples t-test conducted using SPSS, which yielded a significance value of 0.002 (< 0.05). Based on these findings, the RME-based student worksheets can be considered valid, practical, and effective learning materials for enhancing students’ numeracy literacy skills and facilitating their understanding of abstract mathematical concepts through real-life contexts. BAHASA INDONESIA ABSTRACT: Pembelajaran matematika idealnya didukung oleh bahan ajar kontekstual yang membantu siswa memahami konsep dan meningkatkan literasi numerasi. Namun, di MA Mambaul Ulum Banjarejo pembelajaran masih didominasi buku paket yang bersifat abstrak sehingga siswa mengalami kesulitan memahami materi barisan dan deret. Oleh karena itu, diperlukan pengembangan LKPD berbasis Matematika Realistik (RME) yang relevan dengan kehidupan sehari-hari. Penelitian ini bertujuan untuk menghasilkan LKPD berbasis Matematika Realistik yang valid, praktis, dan efektif untuk meningkatkan kemampuan literasi numerasi siswa terhadap materi barisan dan deret. Metode penelitian yang digunakan adalah model pengembangan ADDIE yang meliputi lima tahap: Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi. Partisipan dalam penelitian ini adalah murid kelas X di Madrasah Aliyah Mambaul Ulum Banjarejo. Data dikumpulkan melalui wawancara, observasi, angket, dan tes. Hasil validasi menunjukkan bahwa LKPD tergolong sangat valid pada skala Persentase praktikalitas diperoleh  yang artinya sangat praktis. Implementasi LKPD menunjukkan perbedaan signifikan pada kemampuan literasi numerasi siswa sebelum dan sesudah penggunaan LKPD, yang dibuktikan dengan hasil uji-t berpasangan menggunakan SPSS dengan nilai signifikansi . Berdasarkan hasil analisis, LKPD berbasis RME dapat dikategorikan sebagai media pembelajaran yang valid, praktis, dan efektif dalam mengoptimalkan kemampuan literasi numerasi dan membantu siswa memahami konsep matematika abstrak melalui konteks kehidupan nyata.